Management of virtual private networks for integrated broadband communication. - Schneider, J. M. (Computer communication review.)
Management of Virtual Private Networks (VPNs) is becoming an increasingly important issue in the context of integrated broadband communication (IBC). In the near future corporate customers may want to subscribe to broadband VPN services offered by globally operating service providers to replace most of their leased line services that are used today to build their corporate networks. The concepts historically known as characterizing VPNs, such as the concept of closed user groups, will still be valid, but the importance of VPN service features and, in particular, the set of VPN management services offered to VPN customers will become dominant. In this paper we present a detailed technical approach to the management of broadband VPNs based on current technology and common standards. In particular, we discuss architectural solutions, management interfaces and management services provided at these interfaces, as well as managed objects.